Colonic Inertia: approach and treatment - Soares,Ana Sofia Garcês Ferreira (2017)
ABSTRACT Objective: Revision of the state of the art of the knowledge regarding pathophysiology, diagnosis and treatment of Colonic Inertia, which predominantly affects young women and has a significant socio-economic impact. Methods: A search was made in “colonic inertia”, “colon inertia” and “slow transit constipation” in PubMed database for articles of the last 5 years, in Portuguese or English with available abstract and full text. 59 articles and 2013 guidelines of the American Gastroenterological Association on constipation were included. Results: The pathophysiology is not completely elucidated and the reduction of the interstitial cells of Cajal is the most consistent histological finding. Diagnosis requires the exclusion of secondary causes of constipation and obstructed defecation syndrome, to which contribute several complementary diagnostic tests. Given the frequency of failure of the medical treatment, surgery is often the only possible option. Sacral nerve stimulation seems to be a promising therapeutical alternative. Conclusion: A deeper investigation of the pathophysiological mechanisms is fundamental to acquire a more global and integrated vision. Rigorous patient selection for each treatment and the discovery of new therapeutical targets may avoid the use of surgical therapies.